2017
DOI: 10.1038/srep45256
|View full text |Cite
|
Sign up to set email alerts
|

Serine protease SP105 activates prophenoloxidase in Asian corn borer melanization, and is regulated by serpin-3

Abstract: Melanization reaction, resulting from the activation of prophenoloxidase, is a vital immune response in insects for encapsulating and killing the invasive organisms. Prophenoloxidase needs to be proteolytically activated by its upstream prophenoloxidase-activating protease (PAP) in melanization. Identification and characterization of PAPs facilitates the understanding of the molecular mechanisms involved in insect immunity. We here cloned a full-length cDNA for a serine protease, named as SP105, from Asian cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 58 publications
0
25
0
Order By: Relevance
“…In Bombyx mori, PGRP-S5 functions as a pattern recognition receptor during melanization (23) and BmSPH-1 interacts with PPO and PPO-activating enzyme (PPAE) (24). In Ostrinia furnacalis, SP105 could fucntionaly activate PPO (25). Overall, researches on melanization in other insects are not as comprehensive as those in M. sexta and T. molitor.…”
Section: Introductionmentioning
confidence: 99%
“…In Bombyx mori, PGRP-S5 functions as a pattern recognition receptor during melanization (23) and BmSPH-1 interacts with PPO and PPO-activating enzyme (PPAE) (24). In Ostrinia furnacalis, SP105 could fucntionaly activate PPO (25). Overall, researches on melanization in other insects are not as comprehensive as those in M. sexta and T. molitor.…”
Section: Introductionmentioning
confidence: 99%
“…aegypti rPPO3 ( Aa rPPO3) can also be cleaved by Of SP105. Firstly, recombinant proSP105 was activated by Factor Xa as described previously (Chu et al ., ), and approximately 1.0 µg rPPO3 was added and incubated at room temperature for 1 h. In the control samples, Dm PPO1 was added as a substrate for SP105 (Chu et al ., ), and fungal‐challenged mosquito haemolymph was used to cleave Aa rPPO3. The immunoblot results showed that Of SP105 cleaves rPPO3 into a PO band and an N‐terminal band (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ostrinia furnacalis SP105 (OfSP105) can reportedly cleave and activate D. melanogaster PPO1 (Chu et al, 2017). Here we examined whether Ae.…”
Section: Cleavage Of Rppo3 By Haemolymph and Sp In Vitromentioning
confidence: 99%
See 2 more Smart Citations